2015
DOI: 10.1371/journal.pone.0143388
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection Is Associated with Higher CD4 T Cell Counts and Lower HIV-1 Viral Loads in ART-Naïve HIV-Positive Patients in Ghana

Abstract: BackgroundWorldwide, there is a high co-endemicity of HIV and H. pylori infection and there is growing evidence that H. pylori co-infection is associated with parameters of HIV disease progression. The objective of this study was to investigate the prevalence of H. pylori infection, and the association with clinical, immunological and virological parameters in a large cohort of HIV-infected individuals and uninfected controls in a West African country.MethodsHIV-patients (n = 1,095) and HIV-negative individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 35 publications
5
34
0
2
Order By: Relevance
“…The current study showed that the prevalence of H. pylori infection among HIV infected patients was 17.9%. The finding is lower than the studies reported from Iran (Kafil et al, 2011), India (Nkuize et al, 2010), Ghana (Sarfo et al, 2015), two studies of Nigeria (Anejo-Okopi et al, 2016;Ejilude et al, 2011) and other part of Ethiopia (Teka et al, 2015), which was 69.7, 33, 51.5, 46.8, 47.4 and 64.2%, respectively. Conversely, Perry et al (2006) from Romania, reported low rate, which was 8.3%.…”
Section: Discussionmentioning
confidence: 58%
“…The current study showed that the prevalence of H. pylori infection among HIV infected patients was 17.9%. The finding is lower than the studies reported from Iran (Kafil et al, 2011), India (Nkuize et al, 2010), Ghana (Sarfo et al, 2015), two studies of Nigeria (Anejo-Okopi et al, 2016;Ejilude et al, 2011) and other part of Ethiopia (Teka et al, 2015), which was 69.7, 33, 51.5, 46.8, 47.4 and 64.2%, respectively. Conversely, Perry et al (2006) from Romania, reported low rate, which was 8.3%.…”
Section: Discussionmentioning
confidence: 58%
“…Peripheral blood mononuclear cells (PBMCs) were isolated using the Ficoll centrifugation method and LeucoSep tubes (Greiner Bio One) according to standard protocols. For the HHECO and HISIS cohorts, PBMCs were isolated from 28 HIV-positive blood donors who were recruited from a previously described cohort (HHECO) at the Komfo Anokye Teaching Hospital in Kumasi, Ghana (38,39), and PBMCs from the previously described HISIS cohort (40) were also isolated by centrifugation of heparinized venous blood on a Ficoll-Hypaque (Biocoll separating solution; Biochrom AG, Berlin, Germany) density gradient, prior to cryopreservation.…”
Section: Methodsmentioning
confidence: 99%
“…Ethical approvals for the WHIS and HISIS cohorts were obtained from the Mbeya Regional and National Ethics Committees of the Tanzanian National Institute for Medical Research (NIMR)/Ministry of Health in Dar es Salaam, Tanzania, and from the ethics committee of the University of Munich. The HHECO study was approved by the appropriate ethics committees of the Kwame Nkrumah University of Science and Technology (Ghana) and of the medical association in Hamburg (Germany) (38,39). Signed informed consent was obtained from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Prophylactic Experimental Some clearance in both vaccine and control groups [96] 2012 Intramuscular CagA VacA Nap Alum Prophylactic Experimental Clearance equivalent between vaccine and controls groups [118] 2014 Oral Urease Undisclosed Prophylactic Natural Efficacy, 72% [120] 2015 Oral Urease Undisclosed Prophylactic Experimental Significant prevention of the infection in the children against developing cancers and H. pylori infection. Different virulence factors have been used for constructing high effective vaccines against H. pylori, including urease (UreA and UreB), vacuolating cytotoxin (VacA), neutrophil-activating protein (NapA), CagA, heat shock proteins (Hsps), and different types of outer membrane protein (Omps) [125,126]. A chimeric vaccine, consisting of UreA and UreB, was constructed and expressed in E. coli.…”
Section: References Year Routementioning
confidence: 99%